Adverse health effects of emerging contaminants on inflammatory bowel disease - Chen, Xuejie; Wang, Sidan; Mao, Xueyi; Xiang, Xin; Ye, Shuyu; Chen, Jie; Zhu, Angran; Meng, Yifei; Yang, Xiya; Peng, Shuyu; Deng, Minzi; Wang, Xiaoyan (Frontiers in Public Health, 2023)
Inflammatory bowel disease (IBD) is becoming increasingly prevalent with the improvement of people’s living standards in recent years, especially in urban areas. The emerging environmental contaminant is a newly-proposed concept in the progress of industrialization and modernization, referring to synthetic chemicals that were not noticed or researched before, which may lead to many chronic diseases, including IBD. The emerging contaminants mainly include microplastics, endocrine-disrupting chemicals, chemical herbicides, heavy metals, and persisting organic pollutants. In this review, we summarize the adverse health effect of these emerging contaminants on humans and their relationships with IBD. Therefore, we can better understand the impact of these new emerging contaminants on IBD, minimize their exposures, and lower the future incidence of IBD.